Evaluation of a metal acrylic repair product as a clamp for an external fixator - Staudte, K. L.; Gibson, N. R.; Read, R. A.; Day, R.; Robertson, I. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Mechanical testing was performed to evaluate an acrylic steel repair paste when used in the construction of external fixators. Individual pin-bar-acrylic constructs were compared with those made from Kirschner-Ehmer (KE) clamps or polymethylmethacrylate. The constructs were subjected to cantilever bending forces, pin-pullout tests and cantilever bending after undergoing cyclical fatigue. Forty mm segments of acrylic were significantly stronger than medium ESF clamps. Twenty-five mm segments of acrylic were of equivalent strength to clamps. Ten mm segments failed under physiological loads expected from dogs greater than 20 kg and were less likely to provide adequate pin coverage to protect against pin pull-put. The placement of a wire loop to secure the pin-bar intersects made application of the acrylic easier but did not alter stiffness. There was not any significant variation between different operators in the strength of their constructs nor tolerance of their constructs to pin pullout. Cyclical loading forces were applied to acrylic-pinbar units without significant loss of strength, and acrylic and polymethylmethacrylate units did not show any difference in stiffness after being subjected to cyclical fatigue. The acrylic steel repair paste is a handkneadable, fast setting, inexpensive and readily available acrylic for use in the construction of external fixators. It allows more flexibility in frame design than a clamp and on the basis of mechanical testing offers a very stiff and secure substitute for KE clamps or polymethylmethacrylate.
Keywords: Acrylic; polymethylmethacrylate; fixator; clamp